2017
DOI: 10.1111/scs.12550
|View full text |Cite
|
Sign up to set email alerts
|

Does informal caregiving affect self‐esteem? Results from a population‐based study of individuals aged 40 and over in Germany from 2002 to 2014

Abstract: Our longitudinal study emphasises that the occurrence of informal caregiving did not affect general self-esteem longitudinally. Further research is needed in other cultural settings using panel data methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Despite having a lack of supporting evidence from other studies within the review, the selection of these mental health constructs among studies suggests their relevance within the caregiving context. Specifically, guilt, self-efficacy and self-esteem have all previously been highlighted as themes arising from caregiving experiences, including but not limited to dementia [72][73][74]. The paucity of studies that have taken on a sex and gender lens when examining these constructs reflect the current emergence of sex-and gender-based analysis in this area.…”
Section: Plos Onementioning
confidence: 99%
“…Despite having a lack of supporting evidence from other studies within the review, the selection of these mental health constructs among studies suggests their relevance within the caregiving context. Specifically, guilt, self-efficacy and self-esteem have all previously been highlighted as themes arising from caregiving experiences, including but not limited to dementia [72][73][74]. The paucity of studies that have taken on a sex and gender lens when examining these constructs reflect the current emergence of sex-and gender-based analysis in this area.…”
Section: Plos Onementioning
confidence: 99%
“…While investigating health care among older adults, it was strongly recommended to include psychological factors such as loneliness and self-esteem (Bock et al, 2018). Furthermore, potential negative associations between informal caregiving mode and self-esteem (Hajek & Konig, 2018), as well as anxiety, depression, and PFC (Sörensen et al, 2012), were also reported. From the perspectives of coping appraisal, external support was the main source of support against the threat of disability for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Başkalarının değerlendirme ilkesi, sosyal karşılaştırma ilkesi ve kişinin kendisini değerlendirme ilkesi (Hajek & König, 2017;Johnson, 2012). Rosenberg, öz-saygınlık kavramını üç bölümde incelemektedir: (a) Mevcut saygınlık; bireyin sahip olduğu belirgin kişilik ve fiziksel özellikleridir.…”
Section: öZ-saygınlıkunclassified